2017
DOI: 10.1002/lio2.122
|View full text |Cite
|
Sign up to set email alerts
|

Head and neck paragangliomas: A two‐decade institutional experience and algorithm for management

Abstract: ObjectivesParagangliomas of the head and neck and cranial base are typically benign, slow‐growing tumors arising within the jugular foramen, middle ear, carotid bifurcation, or vagus nerve proper. The objective of this study was to provide a comprehensive characterization of our institutional experience with clinical management of these tumors and posit an algorithm for diagnostic evaluation and treatment.MethodsThis was a retrospective cohort study of patients undergoing treatment for paragangliomas of the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
49
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 38 publications
9
49
0
10
Order By: Relevance
“…Based on our reported incidence rate (2.59 second primary paragangliomas of the chest, abdomen or pelvis per 1000 person‐years), 38 patients would have to get a decade of annual MRIs of the chest, abdomen, and pelvis to identify a single second paraganglioma. Given the growing demand for medical financial stewardship, the cost of such screening appears to exceed the potential benefit, especially as many paragangliomas are ultimately observed without intervention . Alternatively, the use of assays of plasma or urinary catecholamines may be of greater value .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our reported incidence rate (2.59 second primary paragangliomas of the chest, abdomen or pelvis per 1000 person‐years), 38 patients would have to get a decade of annual MRIs of the chest, abdomen, and pelvis to identify a single second paraganglioma. Given the growing demand for medical financial stewardship, the cost of such screening appears to exceed the potential benefit, especially as many paragangliomas are ultimately observed without intervention . Alternatively, the use of assays of plasma or urinary catecholamines may be of greater value .…”
Section: Discussionmentioning
confidence: 99%
“…Given the growing demand for medical financial stewardship, the cost of such screening appears to exceed the potential benefit, especially as many paragangliomas are ultimately observed without intervention. 20 Alternatively, the use of assays of plasma or urinary catecholamines may be of greater value. 19,21 The utility of biochemical screening was not examined in this study but would benefit from further research.…”
Section: Discussionmentioning
confidence: 99%
“…SDHAF2 encodes a mitochondrial protein involved in the flavination of a succinate dehydrogenase complex subunit and it has largely been associated with paragangliomas in previous literature [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…They further mentioned that the most common mode of treatment is surgical excision with preoperative embolization. The resultant complications include complete unilateral vagal nerve paralysis together with additional glossopharyngeal, hypoglossal nerve, and cervical sympathetic chain disturbances [ 5 ]. Heyes et al suggested that surgical excision is the standard treatment of choice for most vagal schwannomas but they stressed that nowadays, the contemporary management evolves toward a conservative modality due to high morbidity of the surgery.…”
Section: Discussionmentioning
confidence: 99%